The Effect of Organic Fertilizer and Time Watering Interval on Growth and Yield of Lettuce (Lactuca sativa L. - Ida Hodiyah; Suhardjadinata Suhardjadinata; Dika Iskandar (Jurnal Agroekoteknologi, 2022)
Plant requires water and fertilizer for its growth. Water plays a role in maintaining cell turgidity or metabolism process especially in photosynthesis. Either organic fertilizer provides nutrients for plants, it is also known that organic fertilizer has the function of fixing soil physical properties by improving soil water holding capacity. The aim of this research is to study the effect of time watering interval and organic fertilizer made from slaughter house waste on lettuce growth and yield. This research was done in greenhouse scale, at Agriculture Faculty, Siliwangi University Tasikmalaya at an altitude of 356 m above sea level, starting from February to May 2020. This research was arranged on Completely Randomized Block Design in factorial pattern, consisted of two factors. The first factor is time watering interval, consisted four time watering intervals, i.e. 1, 2, 3, 4 days. The second factor is organic fertilizer dosage, consisted of five organic fertilizer dosages, i.e. 0 t/ha, 10 t/ha, 20 t/ha, 30 t/ha and 40 t/ha. Each treatment is replicated 3 times, therefore, overall there is 60 experimental units. Data were analysed using analysis of variance with F test and continued by Duncan’s Multiple Range Test with 5% of critical value. The result of this research shows that there is no interraction between time watering interval and slaughter house organic fertilizer on growth and yield of lettuce (Lactuca sativa, L.). The treatment of time watering interval every 3 days and 40 t/ha organic fertilizer tends to produce better growth and yield of lettuce.